2019
DOI: 10.1002/nop2.385
|View full text |Cite
|
Sign up to set email alerts
|

Balancing workload of nurses: Linear mixed effects modelling to estimate required nursing time on surgical wards

Abstract: AimQuantifying the relation between patient characteristics and care time and explaining differences in nursing time between wards.DesignAcademic hospital in the Netherlands. Six surgical wards, capacity 15–30 beds, 2012–2014.MethodsLinear mixed effects model to study the relation between patient characteristics and care time. Estimated marginal means to estimate baseline care time and differences between wards.ResultsNine patient characteristics significantly related to care time. Most required between 18 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…2. During the observational study period, a previously determined set of relevant patient characteristics were registered each dayshift for all patients admitted on the study wards [57]. This information was combined with the work sampling results and a linear mixed effects model was used to determine significance and care time estimates for each characteristic [57,58].…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…2. During the observational study period, a previously determined set of relevant patient characteristics were registered each dayshift for all patients admitted on the study wards [57]. This information was combined with the work sampling results and a linear mixed effects model was used to determine significance and care time estimates for each characteristic [57,58].…”
Section: Data Collectionmentioning
confidence: 99%
“…This method consists of 7 steps to calculate workload. Steps 1 to 4 were elaborated upon in previous publications [31,56,57] and in this paragraph we will briefly explain these steps. Steps 5 to 7 will be discussed in depth in this paper.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The resulting tted model demonstrated an R 2 value ranging from 60-64% (12). According to Oetelaar et al, nine patient characteristics and nurse pro ciency were signi cantly related to nursing workload, with these variables explaining up to 36% of the variance (13). However, the indicators of workload in uencing factors in these two studies were not comprehensive.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have confirmed high workload as a predictor for burnout, which in turn may lead to reduced professional efficacy, poor quality of care and employees quitting their job (Dall'Ora et al, 2020). Allocating workload in such a way that it is balanced between different groups of employees is an important measure which hospitals can take to improve working conditions (van den Oetelaar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%